L’accompagnement entrepreneurial dans le cadre des pépinières et centres d’appui - Une étude de cas dans L’Est Algérien: Entrepreneurial support in the frame of business incubators and support Centers - A case study in Eastern Algeria - GHERRAS Nahla, (Journal of North African Economies, 2025)
The aim of this article is to shed light on the incubators’ performance: « Business incubators and support centers » in supporting SMEs/SMIs (case of eastern Algeria). The survey covered 04 business incubators and support centers out of the 06, covering eastern Algeria. It concerns: Batna, Khenchela, Mila and Oum el Bouaghui. The choice of these cities is not fortuitous. These are the only cities that gather both business incubators and support centers in the East. Semi directive interviews were carried out with incubator managers. Interview analysis allowed the highlight of all the constraints and malfunctions identified during the investigation and that impeded local support structure activity « business incubators and support centers » in SMEs/SMIs creation and development in the eastern cities, specifically their implantation far from the cities, thus discouraging project promoters from moving, the drastic lack of financial means hindering their work, the level of training of these incubators being inappropriate with the training in Management and entrepreneurship that the incubatees really need